Permasalahan Konversi Lahan Pertanian dan Implikasinya Terhadap Penataan Ruang Wilayah Studi Kasus: Wilayah Pantura Jawa Barat - Kustiwan, Iwan (Journal of Regional and City Planning, 1997)
The phenomenon of land conversion to non agricultural use which is occuring rapidly in Java has drawn large attention since it is related to wide dimension of problems, both macro and micro. This article assesses further the conversion of agricultural land in Pantura Jawa Barat by identifying problems and factors influencing the conversion and its implication to the regional spatial planning. In macro perspective, the conversion is an implication of the dynamism of urban growth in Pantura Jawa Barat. External factors considered to have some influences on this conversion are the growth of built area, the growth of urban population, amd the growth and shift of regional economic structure. Whereas in micro perspective the conversion is influenced by internal factors within the farming households, such as the growth of farming households utilizing agricultural land and changes in land owned by the farming households which indicate the increase in the process of land fragmentation.The tendency and the spatial pattern of agricultural land conversion are influenced also by government policy. There are three government policies considered as the driving force for the conversion of agricultural land: the privatization of industrial estate development, the development of large scale settlement and new towns, and deregulation of investment and permit. The policy for controlling the conversion of agricultural land will have macro and micro implications, in relation with the existence of farming households utilizing land. Another implication is related with the control of spatial use as mentioned in Law No.24/1992 about Spatial Planning. The main instruments in controlling spatial use are: Regional Spatial Plan (RTRW) and the mechanism of location permit.